Prevalence and clinical significance of anti-cyclic citrullinated peptide antibodies in juvenile idiopathic arthritis. Issue 7 (1st July 2002) - Avčin, T; Cimaz, R; Falcini, F; Zulian, F; Martini, G; Simonini, G; Porenta-Bešic, V; Cecchini, G; Borghi, M O; Meroni, P L
Abstract : Background: Antibodies against cyclic citrullinated peptide (anti-CCP) are considered to be specific for rheumatoid arthritis (RA). Objective: To assess the clinical significance of anti-CCP in a cohort of patients with juvenile idiopathic arthritis (JIA). Methods: Anti-CCP were tested by an enzyme linked immunosorbent assay (ELISA) in serum samples from 109 patients with JIA (30 boys, 79 girls), with a mean age of 8.7 years (range 0.6–20.3) and mean disease duration of 3.6 years (range 3 months to 15.6 years). As control groups, anti-CCP were also tested in sera of 30 healthy children, 25 patients with juvenile onset systemic lupus erythematosus (SLE), and 50 adult patients (30 with RA, 20 with SLE). Results: Positive anti-CCP values were found in sera of two patients with JIA (2%), one with polyarthritis, and one with oligoarthritis. Statistical analysis showed that anti-CCP were not associated with the presence of antinuclear antibodies, raised erythrocyte sedimentation rate, or erosions. In the control groups, none of the patients with juvenile onset SLE and only one of 20 adults with SLE were positive for anti-CCP, but 19/30 (63%) adults with RA showed anti-CCP positivity. Conclusions: Anti-CCP can be detected in children with JIA, but are less frequently present than in adults with RA.